Anxiety and surplus in nursing practice: lessons from Lacan and Bataille. (27th January 2014) - Evans, Alicia M.; Glass, Nel; Traynor, Michael
Abstract It is well established, following Menzies' work, that nursing practice produces considerable anxiety. Like Menzies, we bring a psychoanalytic perspective to a theorization of anxiety in nursing and do so in order to consider nursing practice in the light of psychoanalytic theory, although from a Lacanian perspective. We also draw on Bataille's notion of 'surplus'. These concepts provide the theoretical framework for a study investigating how some clinical nurses are able to remain in clinical practice rather than leave the profession or seek work at a distance from the bedside. We conducted focus groups and present here an analysis of two fragments of nurses' speech. We found the nurses responded from one of two positions. In the first position, the nurses focus on doctors, complain about the surplus afforded them, and call for it to be eliminated. In this way, the nursing group is similar to other groups, considered by Bataille, who also attempt to get rid of a surplus. However, in the second position, the nurses stay with the surplus, tolerating it as they nurse the patient. This latter position is one where the nurse practises with a focus on the patient rather than being distracted by their dispute over the doctor's privilege. The importance of this paper is in its illustration of two distinct positions from which the nurse can practise: one that is not optimal because the nurse is distracted and the other that is more focused on practice, and thus the nurse is in a position to provide the best care possible to patients.